Profilbővítés és útkeresés a 90 éves Debreceni Nyári Egyetemen, 2000 után (Szubjektív összefoglaló egy évforduló kapcsán) - Szaffkó, Péter (Gerundium, 2017)
Changes and New Developments after 2000 at Debrecen Summer School celebrating its 90th Anniversary. The author (currently acting as Managing Director of Debrecen Summer School) takes a subjective look at those changes and new developments which have expanded and enriched the traditional activities of this unique institution since the end of the 20th century. Providing a brief summary of the decades before 2000 when DSS became an independent non-profit public company, the article intends to give anoverview of some of the major steps taken by the former and current managements which seem to have strengthened the position of the School in the field of promoting Hungarian language and culture. In addition to opening a new school in Budapest in 2002 and introducing special courses in the spring, autumn and winter, DSS has found various ways of cooperating with the University of Debrecen as well as offering semester courses on some of the so-called less widely used and learnt languages such as e.g. Czech, Norwegian, Romanian, Swedish or Turkish. One of the most extensive recent activities would include a wide range of international cooperation based on different kinds of European project applications such as Erasmus+ and the Visegrad Fund. The main aim of the article is to show that the 90-year-old institution is still a living organism which has always tried to live up to the expectations of the age in making Hungarian language and culture attractive to as many people as possible.